Challenges and potential barriers to the uptake of antiretroviral-based prevention in Asia and the Pacific region - Ying Ru Lo (2018)
Evidence has emerged over the past few years on the effectiveness of antiretroviral-based prevention technologies to prevent (i) HIV transmission while decreasing morbidity and mortality in HIV-infected persons, and (ii) HIV acquisition in HIV-uninfected individuals through pre-exposure prophylaxis (PrEP). Only few of the planned studies on treatment as prevention (TasP) are conducted in Asia. TasP might be more feasible and effective in concentrated rather than in generalised epidemics, as resources for HIV testing and antiretroviral treatment could focus on confined and much smaller populations than in the generalised epidemics observed in sub-Saharan Africa. Several countries such as Cambodia, China, Thailand and Vietnam, are now paving the way to success. Similar challenges arise for both TasP and PrEP. However, the operational issues for PrEP are amplified by the need for frequent retesting and ensuring adherence. This paper describes challenges for the implementation of antiretroviral-based prevention and makes the case that TasP and PrEP implementation research in Asia is much needed to provide insights into the feasibility of these interventions in populations where firm evidence of 'real world' effectiveness is still lacking. © 2014 CSIRO.